X-ray structure, surface analyses, spectroscopic characterization, antimicrobial activity and DFT studies of the triphenylphosphoranylidene derivative. (13th November 2020) - İnkaya, Ersin; Eryılmaz, Serpil; Akdemir, Nesuhi; İdil, Önder
Abstract: The structure of 1-(2-hydroxyphenyl)-2-(triphenylphosphoranylidene)ethanone was crystallized. X-ray diffraction, FT-IR, NMR ( 1 H, 13 C, 31 P) and theoretical DFT method were used for understanding structural, electronic, and spectroscopic properties. The theoretical calculation was performed by the DFT method with the B3LYP/6-311G(d, p) basis set. The commentate of both experimental and theoretical results, it was observed good agreement with each other. Vibrational modes and wavenumbers as well as their intensities were performed with the aid of the potential energy distribution (PED) analysis. 1 H, 13 C, and 31 P NMR spectra's have been calculated by employing the gauge-independent atomic orbital method. Also, Hirshfeld and MEP surface analyses, HOMO–LUMO orbitals and Mulliken charge distribution of the triphenylphosphoranylidene derivative were performed. Antibacterial activities of the title compound were tested according to the minimal inhibitory concentration (MIC) method.